2011
DOI: 10.1111/j.1365-2486.2011.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of assisted colonization strategies under global change for a rare, fire‐dependent plant

Abstract: As a clear consensus is emerging that habitat for many species will dramatically reduce or shift with climate change, attention is turning to adaptation strategies to address these impacts. Assisted colonization is one such strategy that has been predominantly discussed in terms of the costs of introducing potential competitors into new communities and the benefits of reducing extinction risk. However, the success or failure of assisted colonization will depend on a range of population-level factors that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 68 publications
(87 reference statements)
0
69
0
Order By: Relevance
“…They require sufficient time between fires to develop an adequate seed bank and are therefore sensitive to too-frequent fire (Keeley 1986). For obligate-seeding, long-lived trees and shrubs (Table 2), we constructed a spatially explicit stochastic age-based matrix model, with age classes ranging from seedlings to plants > 99 years old Regan et al 2010Regan et al , 2012. Survivorship was estimated by fitting functions to published data for the focal species or closely related species.…”
Section: Population Viability Analysis: the Impact Of Threats And Effmentioning
confidence: 99%
See 2 more Smart Citations
“…They require sufficient time between fires to develop an adequate seed bank and are therefore sensitive to too-frequent fire (Keeley 1986). For obligate-seeding, long-lived trees and shrubs (Table 2), we constructed a spatially explicit stochastic age-based matrix model, with age classes ranging from seedlings to plants > 99 years old Regan et al 2010Regan et al , 2012. Survivorship was estimated by fitting functions to published data for the focal species or closely related species.…”
Section: Population Viability Analysis: the Impact Of Threats And Effmentioning
confidence: 99%
“…We found that assisted colonization could minimize risk of decline or extinction for Tecate cypress when: (1) large source populations are projected to decline dramatically due to habitat contractions, (2) multiple nearby sites are predicted to contain suitable habitat, (3) the species has minimal natural dispersal, (4) rates of successful establishment of translocated individuals are high, and (5) non-climatic threats such as altered fire regimes are absent (Table 2). However, when serious ongoing threats exist, such as too-frequent fire, assisted colonization is ineffective at boosting population numbers (for details see Regan et al 2012).…”
Section: Assisted Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (105,108). PVA can also be used to evaluate the efficacy of adaptation measures such as fire management, invasive species control, and managed relocation (109,110).…”
Section: Accounting For Dispersal Limitations When Predicting Speciesmentioning
confidence: 99%
“…Recently, population models have been coupled with species distribution models and threat distribution to investigate expected responses by populations to changing threats and likely actions (e.g. Regan et al 2012). Alternatives to the conventional approach of additive threat mapping depend on the problem scale and constraints.…”
Section: Threat Maps Are Not a Panacea: Improvements To Using Threat mentioning
confidence: 99%